Investment practices of endowment funds in higher education: lessons for the developing world - Mustaffa Kamil, Nazrol Kamil; Haneef, Mohamed Aslam (Centre for Islamic Economics (CIE) Kulliyyah of Economics and Management Sciences (KENMS), International Islamic University Malaysia (IIUM), 2016)
1. Introduction Public funding of higher education has been a very important issue in economically developing countries. As one of the ways to institute social mobility, education and especially higher education is a central public policy agenda. However, in the last two decades or so, public debt levels as well as increasing demands for public funding have required alternative sources of funds. The private sector has played a role and there is a significant presence of private higher education institutions in most, if not all countries with many successful examples that one could cite. However, seen as a ‘public good’ and as an effective means of social mobility and development, ‘profit motivated private higher education’ raises many challenges such as its costs and access. While mainstream economics posit a public-private conflict model, a three sector model that has a positivecomplimentary role for the not-for-profit or voluntary sector offers not only an economically viable alternative, but an ethically superior one. In the context of higher education, the role of foundations and endowment funds in particular has become the focus of attention for researchers. Historically, foundations and endowments were always related to universities. This tradition has actually continued throughout the decades, albeit in a lesser degree. Foundations and endowments have always been a significant source of funding for scholarships, professorships, academic programs, scientific researches, and other operational activities in universities. In many cases, a significant portion of universities’ operating budget is financed through endowment funds. For instance, as the largest university endowment fund in the US and Canada, Harvard University covered its operating expenses by 36% from its endowment fund (Harvard Financial Report, 2013).